Pengetahuan Investasi, Modal Minimal, Uang Saku dan Minat Mahasiswa Menjadi Investor Muda - Gayatri, Ni Gusti Ayu; Gayatri, Gayatri (E-Jurnal Akuntansi, 2022)
KSEI's Public Statistics data shows an increase in the SID of securities, which is dominated by young people. This study aims to determine the interest of students to become young investors. The sample collection used purposive sampling technique and produced a sample of 86 students. Questionnaire answers were processed using Smart-PLS version 3. The results of the study proved that investment knowledge, minimum capital, and pocket money had a positive effect on students' interest in becoming young investors. Research can be considered in making investment decisions as well as for universities, BEI, and interested parties as an effort to increase awareness about the importance of investment knowledge and the number of young investors in Indonesia. Keywords: Young Investors; Pocket Money; Interest